GEBRAK (Gerakan Buruh Bersama Rakyat) dalam Melaksanakan Demonstrasi terhadap Penolakan Omnibus Law Undang-Undang Cipta Kerja - Rahmani, Allyah Nur; Nurlita, Dwie Shinta; Muradi (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to examine the role of the Joint Labor Movement (GEBRAK) as a representative of civil society in organizing demonstrations against the 2020 Omnibus Law on Job Creation. This study uses a descriptive qualitative approach with a literature review method, through searching various academic literature, policy documents, and relevant online news sources. Based on the results of the study, it is known that the formation of the Job Creation Law has caused widespread rejection from the public because it is considered non-participatory, non-transparent, and detrimental to labor groups through the elimination of a number of basic labor rights. GEBRAK emerged as a cross-sector alliance that brought together labor unions, students, activists, and other civil society organizations to articulate public aspirations through demonstrations, legal advocacy, and media campaigns. As a force of civil society, GEBRAK plays an important role in safeguarding participatory democracy by asserting the rights of citizens to voice their opinions and monitor government policies. This movement not only demonstrates resistance to neoliberal policies that are considered unfair, but also symbolizes the growing political awareness of society in the era of Indonesian democracy. This study confirms that the demonstrations carried out by GEBRAK are a concrete manifestation of the function of civil society in maintaining a balance between state power and the aspirations of the people.